Regulation of Corporate Criminal Liability According To Law Number 1 Year 2023 On The Criminal Code - Joko Sriwidodo; M.S. Tumanggor (KRTHA BHAYANGKARA, 2024)
Corporation as a subject of criminal law that can be held criminally responsible is not known in the old Criminal Code. This is because the old Criminal Code is a legacy of the Dutch colonial government whose legal system adheres to the Continental European legal system (civil law). Countries that adhere to the civil law legal system are a little behind in terms of regulating corporations as subjects of criminal law, in contrast to countries that adhere to the common law legal system, which has regulated corporate liability and this has started since the industrial revolution. In Indonesia itself, the regulation on corporation as a subject of criminal law is regulated in the Law outside the Criminal Code. Meanwhile, the new Criminal Code has regulated corporations as legal subjects that can be held criminally liable. As regulated in Article 45 to Article 50, Article 56, and Articles 118 to 124 of Law No. 1 of 2023 on the Criminal Code. Although prior to the enactment of Law No. 1 of 2023 on the Criminal Code there was already Perma No. 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations and Regulation of the Attorney General of the Republic of Indonesia Number PER-28/A/JA/10/2014 concerning Guidelines for Handling Criminal Cases with Corporate Legal Subjects. Prior to the issuance of the regulation, the Attorney General's Office had first issued Circular Letter of the Attorney General of the Republic of Indonesia Number B-036/A/FT.1/06/2009 regarding Corporations as Suspects/Defendants in Corruption Crimes addressed to the Head of High Prosecutors throughout Indonesia. Thus, Corporations as a subject of criminal law can already be held criminally liable with the strength and legal certainty stipulated in the New Criminal Code.